2022
DOI: 10.1186/s12882-022-02674-1
|View full text |Cite
|
Sign up to set email alerts
|

Fasting during Ramadan and acute kidney injury (AKI): a retrospective, propensity matched cohort study

Abstract: Background During the month of Ramadan, Muslims abstain from daytime consumption of fluids and foods, although some high-risk individuals are exempt. Because fasting's effects on the risk of acute kidney injury (AKI) have not been established, this study assesses the relationship between fasting and risk of AKI and identifies patients at high risk. Methods A single-center, retrospective, propensity-score matched, cohort study was conducted with dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Also, the relationship between fasting and the risk of AKI and identified patients at high risk was assessed in a single-center, retrospective, propensity-score-matched cohort study using data collected from adult patients admitted to the ED during Ramadan the following month over two consecutive years (2016 and 2017). 60 A total of 1,199 patients were included; each cohort had 499 patients after matching. In the fasting cohort, the incidence of AKI and the risk of developing AKI were significantly lower (adjusted odds ratio [AOR] 0.65).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the relationship between fasting and the risk of AKI and identified patients at high risk was assessed in a single-center, retrospective, propensity-score-matched cohort study using data collected from adult patients admitted to the ED during Ramadan the following month over two consecutive years (2016 and 2017). 60 A total of 1,199 patients were included; each cohort had 499 patients after matching. In the fasting cohort, the incidence of AKI and the risk of developing AKI were significantly lower (adjusted odds ratio [AOR] 0.65).…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37] The first study assessed the relationship between fasting and the risk of acute kidney injury (AKI) to identify patients at high risk in a single-center, retrospective, propensity-score-matched cohort design. 34 Data were collected from adult patients admitted to the emergency room during Ramadan and the following month over two consecutive years (2016 and 2017). A total of 1,199 patients were included; each cohort had 499 patients after matching.…”
Section: Kidneysmentioning
confidence: 99%
“…In Turkish patients (45 fasters and 49 non-fasters CKD, stages 3-5), Kara et al ( 93 ) found no significant changes in eGFR between non-fasters and fasters; however, individuals above the age of 72 appeared to be at a higher risk of renal function impairment than CKD patients under the age of 64. Recently, a retrospective study of 1,199 patients, who were not exempt from Ramadan fasting for 2 years (2016 and 2017), showed fasting significantly reduced the risk of developing ARF, particularly in patients with comorbidities ( 94 ). The authors concluded that Ramadan fasting conferred no negative effects on the majority of patients with comorbid disorders ( 94 ).…”
Section: Religious Fasting Nutrition and Individual Healthmentioning
confidence: 99%
“…Recently, a retrospective study of 1,199 patients, who were not exempt from Ramadan fasting for 2 years (2016 and 2017), showed fasting significantly reduced the risk of developing ARF, particularly in patients with comorbidities ( 94 ). The authors concluded that Ramadan fasting conferred no negative effects on the majority of patients with comorbid disorders ( 94 ). Similarly, following Ramadan fasting, no significant impairment in renal function was found in autosomal dominant polycystic disease patients with early CKD ( 95 ).…”
Section: Religious Fasting Nutrition and Individual Healthmentioning
confidence: 99%